Sepsis Disease and Treatment in Children (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2026)
Sepsis in children remains a critical global health challenge and a leading cause of morbidity and mortality, particularly in neonatal and pediatric intensive care settings. It is defined as a life-threatening organ dysfunction caused by a dysregulated host response to infection. Early diagnosis and prompt treatment are crucial for improving survival outcomes and reducing long-term complications. This article reviews the etiology, pathophysiology, clinical manifestations, diagnostic criteria, and modern therapeutic approaches for pediatric sepsis, with a special focus on early recognition and evidence-based management strategies in low- and middle-income countries, including Uzbekistan. Emphasis is placed on antimicrobial therapy, hemodynamic support, and the role of preventive measures in reducing the incidence of sepsis among children.